2011
DOI: 10.1124/mol.111.071076
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that γ-Secretase-Mediated Notch Signaling Induces Neuronal Cell Death via the Nuclear Factor-κB-Bcl-2-Interacting Mediator of Cell Death Pathway in Ischemic Stroke

Abstract: Notch-1 (Notch) is a cell surface receptor that regulates cell-fate decisions in the developing nervous system, and it may also have roles in synaptic plasticity in the adult brain. Binding of its ligands results in the proteolytic cleavage of Notch by the ␥-secretase enzyme complex, thereby causing the release of a Notch intracellular domain (NICD) that translocates to the nucleus, in which it regulates transcription. Here we show that activation of Notch modulates ischemic neuronal cell death in vitro and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 33 publications
4
68
0
Order By: Relevance
“…Similarly, systemic γ-secretase inhibition can provide significant neuroprotection in a model of stroke in mice. 15,41 We further showed that excitotoxic KA treatment leads to increase in phosphorylation of Akt, through PTEN-mediated disinhibition and partially through the activation of PI3Kγ. Our study indicates that PTEN is negatively regulated by canonical Notch signaling in line with repression of PTEN by Hes1.…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, systemic γ-secretase inhibition can provide significant neuroprotection in a model of stroke in mice. 15,41 We further showed that excitotoxic KA treatment leads to increase in phosphorylation of Akt, through PTEN-mediated disinhibition and partially through the activation of PI3Kγ. Our study indicates that PTEN is negatively regulated by canonical Notch signaling in line with repression of PTEN by Hes1.…”
Section: Discussionmentioning
confidence: 84%
“…Notch-1 is a cell surface receptor that regulates cell-fate decisions during neural development, and it may also have roles in synaptic plasticity in the adult brain (Arumugam et al, 2011;VanDussen et al, 2011). Binding of its ligands results in the proteolytic cleavage of Notch by the γ-secretase enzyme complex, thereby causing the release of a Notch intracellular domain (NICD) that translocates to the nucleus, in which it regulates transcription.…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that inactivation of Notch signaling protects neuronal cells from apoptotic death and further brain injury following ischemic stroke. 3 There is a positive correlation between Notch signaling and apoptosis. Thus, the inhibition of Notch signaling is the biological response to radiosurgery, not the secondary negative effect of apoptosis.…”
Section: Radiosurgery Inhibits Notch Signaling In the Rat Avf Modelmentioning
confidence: 99%